The Efficacy of Heat Acclimatization Pre-World Cup in Female Soccer Players - Meylan, César M. P.; Bowman, Kimberly; Stellingwerff, Trent; Pethick, Wendy A.; Trewin, Joshua; Koehle, Michael S. (Frontiers in Sports and Active Living, 2021)
The efficacy of a 14-day field-based heat acclimatization (HA) training camp in 16 international female soccer players was investigated over the following phases: Phase 1: 8-days moderate HA (22.1˚C); Phase 2: 6-days high HA (34.5˚C); Phase 3: 11-days of post-HA (18.2˚C). Heart rate (HR), training load, Tc, and perceptual ratings were recorded throughout. The changes from Baseline (Day -16) in (i) Plasma Volume (PV), (ii): HR during a submaximal running test [HRex] and HR recovery [HRR]), and (iii): pre-to-post Phase 2 (Day 8-13) in 4v4-small-sided-soccer game (4V4SSG) performance were assessed. PV increased by 7.4±3.6% (Standardized Effect [SE]=0.63) from the start of Phase 1 to the end of Phase 2, and this occurred primarily in Phase 1 (SE=0.64). Resting Tc dropped by -0.47±0.29°C (SE=-2.45) from day 1 to day 14. Submaximal running HR response decreased over Phase 2 (HRex; SE= -0.49, HRR; SE=0.53) while the greatest HR improvements from baseline were delayed, occurring 11 days into Phase 3 (HRex; SE=-0.42, HRR; SE= 0.37). The 4v4SSG revealed a moderate reduction in HRex (SE = -0.32) and a large increase in HRR (SE = 1.27) from pre-to-post Phase 2. Field-based HA can induce physiological changes beneficial to soccer performance in temperate and hot conditions in elite females, and the submaximal running test is effective to monitor HRex responses that may have been induced by HA for up to two weeks following heat exposure.